Towards gene therapy for IPEX syndrome. Issue 5 (13th April 2022) - Borna, Simon; Lee, Esmond; Sato, Yohei; Bacchetta, Rosa
Abstract: Immune dysregulation polyendocrinopathy enteropathy X linked (IPEX) syndrome is an uncurable disease of the immune system, with immune dysregulation that is caused by mutations in FOXP3 . Current treatment options, such as pharmacological immune suppression and allogeneic hematopoietic stem cell transplantation, have been beneficial but present limitations, and their life‐long consequences are ill‐defined. Other similar blood monogenic diseases have been successfully treated using gene transfer in autologous patient cells, thus providing an effective and less invasive therapeutic. Development of gene therapy for patients with IPEX is particularly challenging because successful strategies must restore the complex expression profile of the transcription factor FOXP3, ensuring it is tightly regulated and its cell subset‐specific roles are maintained. This review summarizes current efforts toward achieving gene therapy to treat immune dysregulation in IPEX patients. Abstract : Current gene therapy strategies aiming to treat IPEX syndrome, comprise (i) conversion of autologous CD4+ T cells into engineered Treg‐like cells for adoptive transfer and (ii) FOXP3 gene correction or addition in hematopoietic stem and progenitor cells. Humanized mice are good preclinical models to address safety and efficacy.